Reviews of Books and Teaching Materials. (American Statistician, 2013)
The article reviews several books including "The Art of R Programming: A Tour of Statistical Software Design," by Norman Matloff, "Probability, Statistics and Financial Math," by Peter Caithamer and "Statistical Concepts: A Second Course," by Richard G. Lomax and Debbie L. Hahs-Vaughn.